نتائج جراحة المرارة التنظيرية في مشفيي الأسد وتشرين الجامعيين في اللاذقية بين عامي 2010-2017: - سعد, أحمد (Latakia University Journal -Medical Sciences Series, 2018)
تمتلك جراحة المرارة التنظيرية العديد من الميزات التي تجعلها مفضلة على الجراحة المفتوحة مع معدل منخفض لحدوث الاختلاطات. أجريت الدراسة على 877 مريضاً خضعوا لجراحة المرارة التنظيرية في مشفيي الأسد وتشرين الجامعيين في الفترة ما بين 2010-2017 تمت دراسة الطريقة الجراحية المتبعة وأسباب التحويل لجراحة مفتوحة إضافة للاختلاطات الحاصلة أثناء أو بعد الجراحة من حيث نسبة الحدوث وطريقة تدبير الاختلاط المتبعة ونتائج هذا التدبير. كان متوسط أعمار المرضى 46 عاماً، نسبة الإناث 64.5%، مدة العمل الجراحية الوسطية 45 دقيقة. نسبة التحويل لجراحة مفتوحة كانت 2.05% واكثر الأسباب كانت الالتهابات الشديدة "عدم وضوح مثلث كالوت" ثم الشك بالخباثة. أجري استئصال المرارة الجزئي بالتنظير في 1.36% من الحالات وحدثت الاختلاطات أثناء الجراحة في 0.34% من الحالات والاختلاطات التالية للجراحة في 2.16% من الحالات. بتحليل النتائج تبين أن نسب التحويل لجراحة مفتوحة ونسبة حدوث الاختلاطات تقع ضمن النسب المقبولة عالمياً كما أن نتائج تدبير الاختلاطات كانت مرضية وتتوافق مع الطرق المتبعة عالمياً لتدبير الاختلاطات. توصلنا بنتيجة الدراسة أن هذه الجراحة آمنة واختلاطاتها قليلة جداً ونوصي بتطبيقها في مشافينا واقترحنا بعض التوصيات التي يمكن من خلالها تقليل نسبة اختلاطات هذه الجراحة. laparoscopic cholecystectomy has many features that make it preferable to open surgery with a low incidence of complications. The study was conducted on 877 patients who underwent laparoscopic cholecystectomy at Al-Assad and Tishreen hospitals in the period 2010-2017 The surgical method used and the reasons for conversion to open surgery were studied in addition to the complications occurring during or after the surgery in terms of occurrence rate and method of management of complications and the results of this management. The average age of patients was 46 years, the proportion of females was 64.5%, the mean surgical time was 45 minutes. The ratio of conversion to open surgery was 2.05% and the most common cause was severe inflammation, "unclear calot`s triangle" and suspicion of malignancy. Partial laparoscopic cholecystectomy was performed in 1.36% of cases and peroperative complications occurred in 0.34% of cases and postoperative complications in 2.16% of cases. Analysis of the results revealed that the rates of conversion for open surgery and the incidence of complications are within the internationally accepted rates and that the results of management of complications were satisfactory and consistent with the methods used globally to manage complications. We concluded that this surgery is safe and its complications are rare. We recommend applying it in our hospitals . We have suggested some recommendations that can reduce the complications of this surgery.